Developing the Strategic Plan for Pahlevani and Zourkanei Federation - Fahim Pishva; Abbas Nazarian; Amir Hosein Monazami; Meysam Rahimizadeh (Shahid Bahonar University of Kerman, 2021)
The purpose of this study was to develop a strategic plan for Pahlevani and Zourkanei federation in Iran. The statistical population of this study included members of the federation's board of directors, chairmen of the federation committees, heads of provincial councils as well as sports and management elites. 50 experts participated in this study through total sampling approach. According to the results of the research, a total of 18 strengths, 30 weaknesses, 12 opportunities, and 17 threats for Pahlevani and Zourkanei federation were identified and based on the internal and external factors, the strategic position of the Pahlevani and Zourkanei Federation in the WT region was determined. A total of 19 strategies, including five SO strategies, five ST strategies, six WO strategies, and three WT strategies for the Pahlevani and Zourkanei federation, were developed. Therefore, according to the results of SWOT analysis matrix, it is necessary to use more than a defensive or stabilization strategy to manage the development of Pahlevani and Zourkanei federation.